Toward a realistic model for the kinetics of the NO + CO reaction on rhodium surfaces - Avalos, L.A. (2005)
A model for the kinetics of NO reduction by CO on Rh(1 1 1) surfaces is proposed that takes into account recent experimental observations on the formation of an N–NO intermediate as an alternative pathway to produce N2, the formation of N-islands in the adsorbed phase, an increase of the NO dissociation probability with the number of neighboring vacant sites, and the blocking of NO dissociation due to the presence of neighboring co-adsorbed NO and CO species. When all these characteristics are taken into account, the overall behavior of the system in steady-state conditions, calculated through Monte Carlo simulations, is consistent with experimental observations. The effect and importance of each elementary process in the reaction kinetics is discussed.